STRATEGI DINAS PERHUBUNGAN DALAM MENINGKATKAN PELAYANAN PARKIR DI KABUPATEN BOJONEGORO - M. Wafiq Mahbubi; Esa Septian; Sri Kasiami (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine and analyze the strategy of the Department of Transportation in improving parking services in Bojonegoro Regency and find out what further actions are needed by the government in an effort to improve parking services in Bojonegoro Regency through SWOT analysis by looking at internal factors regarding strengths and weaknesses, as well as external factors, namely opportunities (threats) and threats (opportunities) at the Bojonegoro Regency Transportation Office. This research method is a qualitative method with a descriptive approach. Determination of informants in this study using a purposive sampling method. The samples in this study were the Head of the Parking Management Section of the Transportation Agency, parking attendants, and the people of Bojonegoro Regency. The results of this study, the unavailability of electronic parking parking that makes people prefer illegal parking in order to avoid illegal levies or excessive payments, a very strategic strategy was found, namely by providing electronic parking at several parking spots to make it easier for people to make payments and minimize illegal levies which can result in a decrease in local revenue from parking.